A corrosion-resistant coating process for screw products

The coating is prepared by using composite materials made of aluminum alloy and silicon carbide powder and magnetron sputtering method, and the problem of insufficient corrosion resistance of screw products in corrosive gas environments is solved, and the effect of significantly improving mechanical strength and corrosion resistance is achieved.

CN119194362BActive Publication Date: 2025-04-11JIANGSU QINCHENG NEW MATERIAL TECHNOLOGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411676275.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-04-11
Estimated Expiration
2044-11-22

AI Technical Summary

Technical Problem

When used in environments with corrosive gases, existing screw products have insufficient corrosion resistance, resulting in rapid corrosion and short service life.

Method used

The composite material made of aluminum alloy and silicon carbide powder is used as the coating material of the screw. The deposition rate and thickness of the coating are controlled by magnetron sputtering method, and the binding force between the coating and the substrate is improved by the surface treatment of silane coupling agent.

Benefits of technology

The mechanical strength and corrosion resistance of the screws are significantly improved, and the substrate is able to keep the substrate uncorroded while simulating a salt spray environment for 240 hours, and the bonding force and friction resistance of the coating and substrate are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194362B_ABST
    Figure CN119194362B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of coating process technology, and specifically to a corrosion-resistant coating process for screw products. The corrosion-resistant coating of the screw product includes an aluminum / silicon carbide composite material and a surface-treated screw, and the aluminum / silicon carbide composite material is coated on the surface of a screw substrate by a magnetron sputtering method. The present invention controls the process parameters of the aluminum / silicon carbide composite material, so that the composite material has high mechanical strength; the present invention uses a magnetron sputtering method to control the process parameters, and the deposition rate of the coating obtained is high; the present invention changes the type of aluminum base in the composite material and controls the sputtering power, so that the aluminum / silicon carbide coated screw has good corrosion resistance; the present invention uses a silane coupling agent to treat the surface of the screw substrate and controls the processing parameters, so that the bonding ability of the obtained coating and the screw is improved; the present invention increases the friction resistance of the screw substrate by using a coating prepared by using α-Si / C and aluminum alloy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coating processes, and in particular to a corrosion-resistant coating process for screw products. Background Art

[0002] Screws are a general term for fasteners. Screws are an indispensable industrial necessity in daily life: for example, cameras, glasses, clocks, electronics, etc. use very small screws; televisions, electrical products, musical instruments, furniture, etc. use general screws; as for engineering, construction, bridges use large screws and nuts; transportation equipment, airplanes, trams, cars, etc. use both large and small screws.

[0003] Since screws have important tasks in industry, screw products are widely used in equipment structures in various industries and are affected by the environment of their use scenarios. Different coating materials and different coating processes are required for different use environments to meet the requirements of long-term use. When screw products are used in an environment with corrosive gases, they need to have good corrosion resistance. The methods to improve the corrosion resistance of such products generally include: selecting a corrosion-resistant substrate, performing appropriate surface treatment, optimizing its structure, or using a rust inhibitor.

[0004] There is salt spray gas in the process chamber of some production equipment. Under high working temperature, screw products cannot be used for a long time in it and will corrode and rust quickly. The existing technology uses aluminum implantation to attach aluminum or aluminum alloy to the substrate to form an anti-corrosion layer. Aluminum can quickly react with oxygen in the air to generate aluminum oxide at high temperature, that is, a composite coating composed of aluminum and aluminum oxide will be formed on the surface of the product. This process can improve the corrosion resistance and service life of screw products. However, the characteristics of aluminum coating are that the material is soft and the tensile strength is poor. If the coating is damaged, the product will still be quickly corroded.

[0005] Patent CN117778970A discloses a corrosion-resistant coating process for screw products. The screw substrate is placed in an aluminum implanter for vapor deposition. The Cr target is sputtered first, and then the Al target is sputtered to give it a Cr-Al coating. The high strength of chromium is used in conjunction with aluminum to increase the corrosion resistance of the screw. However, this process method sputters metal targets in batches. Due to the poor compatibility between Cr and Al, the deposition rate is low during actual use, the bonding force is weak, and the outer layer of Cr target is prone to fall off after long-term use, affecting the service life.

[0006] Patent CN107903724A discloses a coating for screws of truck wheel hubs, including resin, nylon and related modification additives. The coating formed by organic polymer materials increases the bonding ability of the coating with the metal to a certain extent; however, the coating does not contain any moisture-resistant and heat-resistant components. Long-term contact of the screws with a moist and hot environment will cause the screws to rust, and the corrosion of the screws will further affect the strength of the coating.

[0007] In the prior art, some screws achieve corrosion resistance by coating zinc-rich coatings during the surface treatment molding process. However, the zinc content in zinc-rich coatings is too high, even accounting for 70-80%, which not only causes a waste of resources, but also gradually weakens the corrosion resistance as the zinc content decreases. The friction formed by the screws during long-term use consumes the surface metal coating. Under long-term use conditions, the metal coating is severely worn, further affecting the corrosion resistance. It is particularly important to produce a coating that has both corrosion resistance and reduces the friction between the coating and the machine, and increases the bonding ability between the coating and the screw substrate.

[0008] Therefore, a corrosion-resistant coating process for screw products is proposed. Summary of the invention

[0009] The purpose of the present invention is to provide a corrosion-resistant coating process for screw products. By using a composite material made of aluminum alloy and silicon carbide powder as a coating material for a screw substrate and controlling process parameters, the mechanical strength of the aluminum / silicon carbide composite material is enhanced, and it is applied to the screw coating to further increase the mechanical strength; by using a magnetron sputtering method, the sputtering power, the distance between the target and the substrate, and the argon gas pressure are controlled, and the deposition rate of the coating is high; by changing the type of aluminum base and the sputtering power, the corrosion resistance of the aluminum / silicon carbide coated screws is improved; by treating the surface of the screw with a silane coupling agent, the bonding force between the aluminum / silicon carbide coating and the screw is improved; by using α-Si / C, the C / Si molar ratio and the aluminum base to silicon carbide mass ratio are controlled, and the aluminum / silicon carbide coating exhibits significantly improved friction resistance.

[0010] To achieve the above object, the present invention provides the following technical solutions:

[0011] A corrosion-resistant coating process for screw products, characterized in that the corrosion-resistant coating process for screw products comprises the following steps:

[0012] The aluminum base and silicon carbide powders are added to a conical mixer, and mechanically mixed in the mixer to obtain a mixed powder; the mixed powder is added to a cold pressing mold, and cold pressed at 100-400 MPa to obtain a cold pressed sample; the cold pressed sample is added to a tubular furnace, and sintered at 400-700° C. for 30-150 min to obtain a sintered sample; the sintered sample is subjected to hot extrusion and heat treatment at a temperature of 350-550° C. to obtain an aluminum / silicon carbide composite material;

[0013] The screw substrate is pretreated to obtain a pretreated screw; a silane coupling agent is added to an ethanol solution and stirred to obtain a silane solution; the pretreated screw is added to the silane solution, a 10% hydrochloric acid solution is added, and the reaction is carried out at 80-120° C. to obtain a reaction system; the reaction system is centrifuged, washed, and dried for 1 hour to obtain a surface-treated screw;

[0014] The aluminum / silicon carbide composite material and the surface-treated screws are added to a radio frequency magnetron sputtering device, and the corrosion-resistant coating screw products are obtained by balancing the equipment air pressure, cleaning the equipment, pumping and filling, pre-sputtering, ignition and deposition, and sputtering sampling;

[0015] The sputtering power is 150-300W, the distance between the target and the substrate is 40-90mm, and the argon gas pressure is 0.5-1.20Pa;

[0016] The mass ratio of the aluminum base to the silicon carbide powder is 1:1-5; the molar ratio of carbon to silicon in the silicon carbide powder is 0.8-1.6:1.

[0017] Preferably, the aluminum base is selected from one of aluminum-magnesium alloy, aluminum-silicon alloy, aluminum-copper alloy, aluminum-zinc alloy, and aluminum metal ball.

[0018] Preferably, the preparation of the surface treated screws comprises the following steps:

[0019] The screw substrate is added to anhydrous ethanol and subjected to ultrasonic treatment for 30 minutes to remove pollutants on the surface of the substrate to obtain an ultrasonic substrate; the ultrasonic substrate is added to a 0.1 mol / L hydrochloric acid solution and soaked for 10 minutes, and then washed with deionized water and dried to obtain the pretreated screw;

[0020] The silane coupling agent was added to the ethanol solution and stirred evenly to obtain a silane solution; the pretreated screws were added to the silane solution, and a 10% hydrochloric acid solution was added, and stirred for 1 hour until the solvent evaporated, washed with deionized water, and vacuum dried at 80° C. for 1 hour to obtain the surface-treated screws.

[0021] Preferably, the silane coupling agent is selected from one of vinyltrimethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, (3-aminopropyl)trimethoxysilane and trimethoxychlorosilane.

[0022] Preferably, the aluminum / silicon carbide composite material is prepared by powder mixing, cold pressing, nitrogen sintering, and hot extrusion.

[0023] Preferably, the cold pressing pressure during the cold pressing process is 100-300 MPa; the nitrogen sintering temperature is 500-650°C, and the sintering time is 30-120 min; and the hot extrusion treatment temperature is 400-500°C.

[0024] Preferably, the preparation of the screw product with the corrosion-resistant coating comprises the following steps:

[0025] Open the vent valve of the vacuum sputtering chamber, balance the air pressure in the furnace with the atmospheric pressure, and then open the furnace door; clean the equipment cavity, the surface of the magnetron target, the sample, the fixture, etc. with alcohol; put the surface-treated screws into a beaker, and ultrasonically clean them with deionized water, acetone, and anhydrous ethanol for 10-15 minutes respectively to obtain a clean substrate; rinse the surface of the clean substrate with flowing anhydrous ethanol for 30-50 seconds, blow dry the cleaned substrate with an ear bulb, immediately place it on the sample holder, load it into the sputtering chamber, close the furnace door, evacuate, and start sputtering deposition;

[0026] Close the furnace door and valve, and start the circulating water system; turn on the gas flow meter power switch, open the gas cylinder, and then turn the flow meter valve to "valve control", adjust the flow rate to maintain 30sccm, and maintain it for 10-15min; slowly pump gas until the gas pressure in the furnace reaches the test working pressure;

[0027] Turn on the sputtering power supply, slowly adjust the gas filling valve until the target surface glows, start pre-sputtering the target, and continue for 10-20 minutes; then adjust the sputtering power and gas pressure, remove the baffle on the surface of the clean substrate, perform sputtering coating, and determine the thickness by recording the sputtering time, and the sputtering time is 6 hours;

[0028] After the experiment, all valves were closed, and the water cooling system was closed after 1 hour. After the reaction device was cooled, the furnace gas valve was opened to balance the atmospheric pressure inside and outside the furnace, and then the furnace door was opened to obtain the screw products with the corrosion-resistant coating.

[0029] Preferably, the sputtering power is 100-250W; the distance between the target and the substrate is 50-80mm; and the argon gas pressure is 0.6-1.0Pa.

[0030] Preferably, the concentration of the silane coupling agent is 0.8-1.5 mg / L.

[0031] A corrosion-resistant coating process for screw products, characterized in that: the corrosion-resistant coating of the screw products comprises the aluminum / silicon carbide composite material and the surface-treated screws; the corrosion-resistant coating of the screw products is obtained by any of the processes described above; the tensile strength of the aluminum / silicon carbide composite material is 262MPa; the coating deposition rate of the corrosion-resistant coated screw products is 1.42μm / h; the substrate of the corrosion-resistant coated screw products is not corroded under the conditions of 240h in a simulated salt spray environment; in a bonding strength test of the corrosion-resistant coated screw products, the bonding strength grade is 5B; the average friction coefficient of the corrosion-resistant coated screw products is 0.125.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] 1. The present invention uses aluminum alloy and silicon carbide powder through mixing, cold pressing, nitrogen sintering, hot extrusion, and heat treatment processes to obtain an aluminum / silicon carbide composite material as a coating material for a screw substrate; during the process preparation process, the process parameter conditions are controlled, and the tensile strength of the obtained aluminum / silicon carbide composite material is 262MPa, showing significantly improved mechanical strength. When used as a coating material in a screw substrate, the mechanical strength of the material can be significantly improved.

[0034] 2. The present invention uses aluminum / silicon carbide composite materials as target materials and surface-treated screws as substrates. By using magnetron sputtering, the sputtering power, the distance between the target material and the substrate, and the argon gas pressure are controlled. The coating deposition rate of the obtained aluminum / silicon carbide coated screws reaches 1.425 μm / h, which has a significantly improved deposition rate.

[0035] 3. The present invention utilizes magnetron sputtering to prepare aluminum / silicon carbide coated screws, changes the coating thickness by adjusting the sputtering power, and simultaneously changes the type of aluminum matrix in the aluminum / silicon carbide composite material. By using different types of aluminum alloys, aluminum silicon alloy is determined to be used, and a dense and continuous aluminum oxide film and silicon oxide film are formed on the surface thereof, thereby producing a good protective effect on the substrate. The corrosion mechanism is a process in which the aluminum oxide film is continuously generated and dissolved, and new and old aluminum oxide films are alternately generated, thereby increasing the corrosion resistance of the screws. The substrate of the obtained aluminum / silicon carbide coated screws is not corroded under the conditions of simulating a salt spray environment for 240 hours, showing significantly improved corrosion resistance.

[0036] 4. The present invention uses methyltrimethoxysilane to perform surface treatment on screws under acidic conditions. The -SiOH produced during the hydrolysis process can undergo a condensation reaction with the hydroxyl group on the metal surface to generate Si-O-Me, thereby firmly combining the silane coupling agent with the metal surface. At the same time, the -SiOH between the methyltrimethoxysilanes can also undergo a condensation reaction to generate Si-O-Si bonds, thereby forming a strong binding organic silane film on the metal surface. The bonding strength grade of the obtained aluminum / silicon carbide coating in the white knife test is 5B, showing a significantly improved bonding ability.

[0037] 5. The present invention uses α-Si / C and utilizes the smooth surface of the Si / C coating under this crystal condition, and at the same time has a self-lubricating effect, thereby improving the corrosion resistance of the coating; by controlling the C / Si molar ratio and the mass ratio of aluminum base to silicon carbide, the average friction coefficient of the obtained aluminum / silicon carbide coated screws is 0.125, showing significantly improved friction resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is a process flow chart of corrosion-resistant coating of screw products of the present invention;

[0039] Figure 2 The corrosion condition diagram of the aluminum / silicon carbide coated screws of Example 31 at 24h, 48h, 120h, and 240h. DETAILED DESCRIPTION

[0040] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0041] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0042] The aluminum-magnesium alloy of the present invention is selected from ZL303, which is purchased from Hebei Jisheng Aluminum Powder Co., Ltd.

[0043] The aluminum-silicon alloy described in the present invention is selected from ZL106, which is purchased from Hebei Jisheng Aluminum Powder Co., Ltd.

[0044] The aluminum-copper alloy of the present invention is selected from ZL207, which is purchased from Hebei Jisheng Aluminum Powder Co., Ltd.

[0045] The aluminum-zinc alloy described in the present invention is selected from ZL402, which is purchased from Hebei Jisheng Aluminum Powder Co., Ltd.

[0046] See also Figure 1 to Figure 2 The present invention provides a corrosion-resistant coating process for screw products, and the technical solution is as follows:

[0047] Examples 1-12

[0048] Aluminum-magnesium alloy and silicon carbide powder are added to a conical mixer at a mass ratio of 1:3, and mechanically mixed in the mixer for 90 minutes to make the particles in the system evenly distributed to obtain a mixed powder; the mixed powder is added to a cold pressing mold, and a hydraulic press is used for cold pressing molding, the cold pressing pressure is 100-300MPa, the cold pressing time is 20s, and a cold pressing sample is obtained; the cold pressing sample is added to a tubular furnace, nitrogen atmosphere, temperature is 500-650℃, heating rate is 10K / min, sintering time is 30-120min, and sintered sample is obtained; the sintered sample is subjected to hot extrusion and heat treatment to obtain the aluminum / silicon carbide composite material, wherein the hot extrusion temperature is 400-500℃. The specific process parameters are shown in Table 1.

[0049] Comparative Example 1 The preparation method and parameter conditions described in Example 1 are referred to, except that aluminum metal balls are used as the aluminum base.

[0050] Comparative Example 2 The preparation method and parameter conditions described in Example 1 are referred to, except that no hot extrusion treatment is performed.

[0051] Example 13 Mechanical Strength Test

[0052] The aluminum / silicon carbide composite materials prepared in Examples 1-12 and Comparative Examples 1-2 were used to prepare test specimens according to the national standard GB / T 7963-2015. The samples after hot extrusion were cut into standard tensile specimens, and their tensile strengths were measured. During the stretching process, reinforcing sheets were used at both ends to prevent the samples from slipping. The test results are shown in Table 1.

[0053] From the results in Table 1, it can be seen that the mechanical strength of the composite material obtained by using metal aluminum balls instead of aluminum alloy in Comparative Example 1 is significantly lower than that of Examples 1-12, indicating that the use of alloy increases the mechanical properties of the aluminum / silicon carbide composite material; in Comparative Example 2, the sintered sample obtained is not subjected to hot extrusion heat treatment, and the mechanical strength of the composite material is more significantly reduced compared with Examples 1-12. Since the SiC particles are evenly dispersed in the aluminum matrix and tightly combined with the aluminum matrix, the density of the composite material is improved, and the lower density will lead to an increase in the pores and defects between the particles in the composite material, causing the composite material to crack or break under external stress, thereby reducing the strength and hardness of the composite material; from the results of Examples 1-3, it can be seen that with the increase of cold pressing pressure, the tensile strength of the composite material shows a trend of first increasing and then decreasing. Due to the increase of cold pressing pressure, high pressure will make the molecules inside the material more densely stacked, reduce the presence of voids and holes, thereby reducing the shrinkage of the material and improving the tensile properties of the material. However, excessive pressure forms a certain internal stress between the powders. During the sintering process, the internal stress inside the sample will cause a certain elastic effect between the powders, resulting in a decrease in the shrinkage ratio of the sample, a decrease in the sample The compactness of the product deteriorates, thereby reducing its tensile strength; it can be seen from the results of Example 2 and Comparative Examples 4-6 that with the increase of sintering temperature, the tensile strength of the composite material is less affected, but too high a temperature will cause excessive reaction of SiC particles with the aluminum matrix, generating harmful phases such as Al4C3, and reducing the application performance of the composite material; it can be seen from the results of Example 2 and Examples 7-9 that with the extension of sintering time, the combination of SiC particles and aluminum matrix can be promoted, and the compactness and mechanical properties of the composite material can be improved, but too long a sintering time will cause partial melting, merging or agglomeration of the matrix alloy, and there is overburning, resulting in reduced mechanical properties of the composite material; it can be seen from the results of Example 2 and Examples 10-12 that with the increase of hot extrusion temperature, the tensile strength of the composite material gradually increases and tends to be unchanged. It can be seen from the results of Table 1 that by changing the preparation process parameters of the composite material, the tensile strength of the aluminum / silicon carbide composite material obtained is 262MPa, showing a significantly improved mechanical strength.

[0054] Examples 14-25

[0055] The screw substrate was added to anhydrous ethanol and ultrasonically treated for 30 minutes to remove pollutants on the surface of the substrate, and then placed in a 0.1 mol / L hydrochloric acid solution and soaked for 10 minutes, and then washed with deionized water and dried to obtain a pretreated screw;

[0056] Adding a silane coupling agent to an ethanol solution and stirring evenly to obtain a silane solution; adding the pretreated screw to the silane solution, adding a 10% hydrochloric acid solution, stirring at 100° C. for 1 hour until the solvent evaporates, washing with deionized water, and vacuum drying at 80° C. for 1 hour to obtain a surface-treated screw;

[0057] The aluminum / silicon carbide composite material prepared in Example 2 was used as a target material; the surface-treated screws were used as a substrate;

[0058] The production process of aluminum / silicon carbide coated screws is as follows:

[0059] Open the vent valve of the vacuum sputtering chamber, balance the air pressure in the furnace with the atmospheric pressure, and then open the furnace door; clean the equipment cavity, the surface of the magnetron target, the sample, the fixture, etc. with alcohol; put the surface-treated screws into a beaker, and ultrasonically clean them with deionized water, acetone, and anhydrous ethanol for 10-15 minutes respectively; prepare a clean substrate; rinse the surface of the clean substrate with flowing anhydrous ethanol for 30-50 seconds, blow dry the cleaned substrate with an ear bulb, immediately place it on the sample holder, load it into the sputtering chamber, close the furnace door, evacuate, and start sputtering deposition;

[0060] Close the furnace door and valves, and start the circulating water system; start the mechanical pump, wait until the vacuum is below 10Pa, and close the bypass valve; start the molecular pump, then open the isolation valve, open the molecular pump gas valve to the maximum, and vacuum to less than 5×10 -3 Start to inflate after Pa; turn on the gas flow meter power switch, open the gas cylinder, then turn the flow meter valve to "valve control", adjust the flow rate to maintain 30sccm, and maintain it for 10-15min; slowly pump gas until the air pressure in the furnace reaches the test working pressure.

[0061] Turn on the sputtering power supply, slowly adjust the inflation valve until the target surface glows, and start pre-sputtering the target for 10-20 minutes, until the color of the glow discharge turns light blue, indicating that the oxides and oil stains on the target surface have been removed; then adjust the sputtering power and gas pressure, remove the baffle on the surface of the clean substrate, perform sputtering coating, and determine the thickness by recording the sputtering time. The sputtering time is 6 hours.

[0062] After the experiment, all valves were closed, and the water cooling system was closed after 1 hour. After the reaction device was cooled, the furnace gas valve was opened to balance the atmospheric pressure inside and outside the furnace, and then the furnace door was opened to obtain aluminum / silicon carbide coated screws. The specific differences are shown in Table 2.

[0063] The production process flow chart of the aluminum / silicon carbide coated screws is as follows Figure 1 As shown; the sampling process in the flow chart is not a continuous operation step, and the sampling can be completed according to time points or batches, which is indicated by dotted arrows in the flow chart. Example 26 Deposition Rate Determination

[0064] The coating thickness was calculated using the weighing method, that is, the screw substrate was weighed before and after deposition, and the deposition rate was calculated according to the following formula. The calculation results are shown in Table 2.

[0065]

[0066] d is the thickness of the aluminum / silicon carbide coating, in μm; m1 is the weight of the screw substrate before deposition, in g; m2 is the weight of the screw substrate after deposition, in g; ρ is the aluminum / silicon carbide density; S is the total surface area of ​​each screw substrate; t is the deposition time, in h; v is the deposition rate, in μm / h.

[0067]

[0068] From the results in Table 2, it can be seen that with the change of sputtering power, gas flow rate and sputtering gas pressure, the deposition rate of the screw substrate is also constantly changing; from the results of Examples 14-17, it can be seen that with the increase of sputtering power, the coating deposition rate tends to increase; due to the increase in power, more particles are sputtered from the surface of the target material per unit area per unit time, the movement speed of the particles is accelerated, the number of particles reaching the surface of the substrate increases, and the energy of the particles is higher, the nucleation rate of the coating increases, and therefore the coating growth rate increases; from the results of Examples 16 and 18-19, it can be seen that with the increase of the target-substrate distance, the deposition rate tends to increase first and then decrease; when the sputtered particles migrate to the surface of the substrate, due to the increase in the target-substrate distance, the probability of collision with the argon molecules in the vacuum chamber increases, resulting in a decrease in the probability of the deposited particles reaching the surface of the substrate, thereby reducing the coating deposition rate; when the target-substrate distance is too small, the distance over which the sputtered ions are accelerated by the electric field is short, the particle energy is small, the nucleation rate decreases, and the coating deposition rate also decreases accordingly. From the results of Examples 16 and 20-21, it can be seen that with the increase of gas pressure, the growth rate of the coating shows a trend of first increasing and then decreasing; as the argon content increases, the gas atoms and ions in the vacuum chamber increase, the number of atomic groups sputtered by the gas particles impacting the target material increases, and the deposition rate is increased; however, when the gas pressure is too high, the number of collisions between the sputtered atomic groups and the neutral argon molecules increases, which will reduce the energy of the ions and atomic groups, and also reduce the reaction rate, and the growth rate of the coating decreases; similarly, to a certain extent, the effect of the argon flow rate on the formation of the coating can be approximately equivalent to the effect of the working gas pressure. When the argon flow rate increases, the probability of the sputtered particles colliding with the argon particles during movement increases, which will also reduce the number of particles reaching the surface of the substrate, resulting in a decrease in the deposition rate; the results of Examples 22-25 further verify the influence of the target-substrate distance and the argon pressure on the deposition rate of the substrate coating; based on the results in Table 2, it can be obtained that by controlling the sputtering power, the target-substrate distance and the argon pressure, the coating deposition rate of the obtained aluminum / silicon carbide coated screws reaches 1.42μm / h, which has a significantly improved deposition rate.

[0069] Examples 27-33 The preparation methods and parameter conditions of Example 16 are referred to, with the differences shown in Table 3.

[0070] Comparative Example 3 The preparation method and parameter conditions are the same as those of Example 16, except that aluminum metal balls are used as the aluminum base.

[0071] Example 34 Corrosion resistance test

[0072] The aluminum / silicon carbide coated screws prepared in Examples 27-33 and Comparative Example 3 were placed in a DG-170211 salt spray corrosion chamber and tested in a 5wt% NaCl solution salt spray environment according to the national standard GB / T 10125-2012 "Artificial Atmosphere Corrosion Experiment Salt Spray Test". The test solution was a 5% NaCl solution with a pH of 6.5-7.2; the test chamber temperature was maintained at (35±1)°C, and the spray was continuously sprayed for 240 hours. The corrosion of the samples was observed, and the corrosion conditions are shown in Table 3; the corrosion conditions of the aluminum / silicon carbide coated screws of Example 31 at 24h, 48h, 120h, and 240h are shown in Table 3. Figure 2 shown.

[0073]

[0074] From the results in Table 3, it can be seen that the aluminum / silicon carbide coated screws made by using the composite material formed by aluminum metal balls and silicon carbide as the corrosion-resistant coating of the screws have obvious corrosion under simulated conditions for 240 hours, showing obvious corrosion phenomena compared with Examples 27-33; It can be seen from the results of Examples 27-30 that with the increase of sputtering power, the deposition rate gradually increases, and at the same time, the thickness of the coating gradually increases. The thin coating shows pitting in the salt spray test, and the pitting continues to develop with time, which is manifested by the increasing number of pitting holes; the number of pitting holes is relatively stable with time, but the pitting pits that have been corroded continue to deepen, and the corrosion continues to develop in depth, eventually corroding the substrate. As the sputtering power increases, the deposition rate increases, and the coating becomes thicker, but this is accompanied by an increase in the number and size of surface sputtering defects. Since sputtering is performed at room temperature and the substrate is not additionally heated, the atomic groups sputtered from the target fall onto the surface of the substrate and cannot diffuse over long distances to form an ordered structure, forming a disordered amorphous layer. The increase in the amorphous layer makes the coating surface rough, and the surface energy of local pits is low, which is preferentially penetrated by chloride ions with high activity and small radius, causing pitting of the coating, corrosion, and coating damage. The corrosive medium penetrates into the surface of the substrate, and then galvanic corrosion is formed, which accelerates corrosion. The results of Examples 29 and 31-33 show that with the change of the type of aluminum base, there is a direct impact on the corrosion performance of the screws. When using aluminum-silicon alloy, a dense and continuous aluminum oxide film and silicon oxide film are formed on its surface, thereby producing a good protective effect on the substrate. Its corrosion mechanism is the continuous generation and dissolution of the aluminum oxide film, and the alternating generation of new and old aluminum oxide films, which increases the corrosion performance of the substrate. By Figure 2The results show that the aluminum-silicon alloy / silicon carbide coating loses its metallic luster after 48 hours, and the surface color continues to deepen thereafter; after 120 hours, the surface becomes obviously gray-black, which is presumed to be due to oxidation and the formation of an oxide film on the surface. As the salt spray test proceeds, the oxide film continues to thicken; due to the dissolution of the oxide film, the coating gradually turns from dark to light after 240 hours, but the coating is still not penetrated. The process of color change on the coating surface is the process of generation and dissolution of the oxide film on the aluminum surface. The substrate does not corrode. Due to the continuous generation and dissolution of the oxide film, the roughness of the coating surface is reduced, which further avoids the corrosion of the substrate by particles; Comprehensive Table 3, Figure 2 The results show that when the sputtering power is controlled at 200W, the substrate of the aluminum / silicon carbide coated screws made of aluminum-silicon alloy is not corroded under the conditions of 240 hours of simulated salt spray environment, showing significantly improved corrosion resistance.

[0075] Examples 35-45

[0076] The screw substrate was added to anhydrous ethanol and ultrasonically treated for 30 minutes to remove pollutants on the surface of the substrate, and then placed in a 0.1 mol / L hydrochloric acid solution and soaked for 10 minutes, and then washed with deionized water and dried to obtain a pretreated screw;

[0077] Add the silane coupling agent to the ethanol solution, stir evenly to obtain a silane solution with a concentration of 0.8-1.5 mg / L; add the pretreated screw to 10 ml of the silane solution, add 5 ml of a 10% hydrochloric acid solution, and stir for 2 hours at 80-120° C. to obtain a reaction solution; spin dry the reaction solution solvent, wash with deionized water, and vacuum dry at 80° C. for 1 hour to obtain a surface-treated screw;

[0078] The production process of aluminum / silicon carbide coated screws refers to the preparation method and parameter conditions of Example 16.

[0079] Comparative Example 4 The preparation method and parameter conditions are the same as those of Example 35, except that no silane coupling agent is added for surface treatment.

[0080] Example 46 Binding Strength Test

[0081] The bonding strength between the coating and the substrate was determined by a grid knife test. According to the standard ASTM D3359 test method, a grid knife with a specification of 1±0.01 mm was used in Examples 35-45 and Comparative Example 4 to evenly cross-cut a grid pattern on the surface of the film layer at a speed of 20-50 mm / s. The cut penetrated the coating, and then a soft brush was used to brush along the diagonal direction of the pattern 5 times each to remove surface dust. Finally, a special tape (3M VHB 4910, with a bonding strength to metal of up to 2600 N / m) was used to cover the entire grid area, and it was quickly torn off at the smallest angle. A magnifying glass was used to observe the integrity of the grid area, and the integrity level of the grid area was determined by Table 4. The test results are shown in Table 5.

[0082]

[0083] The results in Table 5 show that the bonding strength grade of the aluminum / silicon carbide coated screws obtained by surface treatment of the screw substrate without using a silane coupling agent is 2B. After being scratched by a grating knife and the tape sticking, part of the cut edge peels off. Compared with Examples 35-45, a larger area of ​​coating peels off, the bonding strength of the aluminum / silicon carbide coating is poor, and the service life is reduced. By comparing the results of Examples 35-39, it can be seen that the use of different silane coupling agents has a significant change in the bonding strength between the coating and the substrate. The metal will absorb water molecules, and the water molecules will be ionized into hydroxyl groups and metal atoms under the action of metal active atoms to form Me-OH bonds. The silane coupling agent undergoes a hydrolysis reaction under the action of acid to generate silanol, and the -SiOH generated in the hydrolysis process can undergo a condensation reaction with the hydroxyl groups on the metal surface to generate Si-O-Me, which firmly combines the silane coupling agent with the metal surface. At the same time, the -SiOH between the silane coupling agents will also undergo a condensation reaction to generate Si-O-Si bonds, thereby forming a strong binding organic silane film on the metal surface. The regular arrangement of the silane coupling agent bonding on the metal surface greatly increases the uniformity of the organic coating on the metal surface, and improves the corrosion resistance and crack resistance. The properties of siloxane determine the bonding ability between metal and coating. The silicon atoms in aluminum / silicon carbide can covalently bond with Si-O-Si in the silane coupling agent to increase the bonding strength between the coating and the screw substrate. It can be seen from the results of Examples 36 and 40-42 that with the increase of the concentration of the silane coupling agent, the bonding strength shows a trend of first increasing and then decreasing. It can be seen from the results of Examples 36 and 43-45 that with the increase of the curing temperature, the bonding strength gradually increases and tends to remain unchanged. The curing process is mainly cross-linking and polycondensation reactions between silanol molecules. If the curing is not sufficient, a large number of hydrogen bonds will remain on the metal surface. The hydrogen bonds will absorb water in the air, causing the film layer to bubble, and the bonding effect will be greatly reduced. If the curing temperature is too high, the coupling agent will easily turn yellow or even deteriorate, resulting in a decrease in the bonding strength of the subsequent coating. If the curing temperature is too low, due to the high melt viscosity and poor fluidity of the coupling agent, it will not only affect the leveling of the coating and produce pinholes, reduce the corrosion resistance of the coating, but also reduce the bonding strength of the coating. From the results in Table 5, it can be seen that the bonding strength grade of the aluminum / silicon carbide coated screws prepared by magnetron sputtering using methyltrimethoxysilane surface treatment is 5B in the cross-cutting experiment, showing a significantly improved bonding ability.

[0084] Examples 47-55 The preparation methods and parameter conditions of Example 35 are referred to, with the differences shown in Table 6.

[0085] Comparative Example 5 The preparation method and parameter conditions are the same as those of Example 35, except that silicon carbide is not used in the coating preparation process.

[0086] Example 56 Wear resistance test

[0087] The aluminum / silicon carbide coatings prepared in Examples 47-55 and Comparative Example 5 were subjected to friction performance tests using an MMQ-02G high temperature friction and wear tester. After the friction performance test, the wear tester automatically draws a friction curve, and the average friction coefficient is obtained based on the curve. The test results are shown in Table 6.

[0088]

[0089] From the results in Table 6, it can be seen that in Comparative Example 5, only aluminum base is used as the corrosion-resistant coating, and the friction resistance of the aluminum-coated screws obtained is significantly reduced compared with Examples 47-55; Comparative Examples 47-48, the average friction coefficient of α-Si / C is lower than that of β-Si / C, showing more obvious wear resistance; From the results of Examples 47 and 49-52, it can be seen that with the gradual increase of the C / Si molar ratio in silicon carbide, the average friction coefficient of the coating shows a trend of first decreasing and then increasing. Since the surface of the C-rich coating is smooth and has a self-lubricating effect, as the C / Si friction ratio increases, the average friction coefficient of the coating increases. As the ratio of silicon carbide to aluminum increases, the degree of crystallization of the SiC phase in the coating is high, resulting in a decrease in friction performance; compared with the results of Examples 47 and 53-55, it can be seen that as the content of silicon carbide increases, the wear resistance of the coating is enhanced, which is due to the increase in the density of silicon carbide particles, the enhanced protection of the substrate, and the enhanced bonding ability with the substrate surface; however, as the content continues to increase, the average friction coefficient increases and the wear resistance decreases. This is because when the silicon carbide content is too large, the aluminum base content in the coating decreases, and it does not play the role of "fixing silicon carbide particles". The silicon carbide particles fall off seriously, resulting in a decrease in the wear resistance of the coating. From the results of Table 6, it can be seen that the average friction coefficient of the aluminum / silicon carbide coated screws prepared using the composite coating formed by α-Si / C and aluminum silicon alloy is 0.125, showing a significantly improved friction resistance.

[0090] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A corrosion-resistant coating process for screw products, characterized in that: The corrosion-resistant coating process for screw products comprises the following steps: The aluminum base and silicon carbide powders are added to a conical mixer, and mechanically mixed in the mixer to obtain a mixed powder; the mixed powder is added to a cold pressing mold, and cold pressed at 100-400 MPa to obtain a cold pressed sample; the cold pressed sample is added to a tubular furnace, and sintered at 400-700° C. for 30-150 min to obtain a sintered sample; the sintered sample is subjected to hot extrusion treatment at 350-550° C. to obtain an aluminum / silicon carbide composite material; The screw substrate is pretreated to obtain a pretreated screw; a silane coupling agent is added to an ethanol solution and stirred to obtain a silane solution; the pretreated screw is added to the silane solution, a 10% hydrochloric acid solution is added, and the reaction is carried out at 80-120° C. to obtain a reaction system; the reaction system is centrifuged, washed, and dried for 1 hour to obtain a surface-treated screw; The aluminum / silicon carbide composite material and the surface-treated screw are added into a radio frequency magnetron sputtering device, and the screw product with the corrosion-resistant coating is obtained by balancing the equipment air pressure, cleaning the equipment, evacuating and filling, pre-sputtering, ignition and deposition, and sputtering sampling; the aluminum / silicon carbide composite material is prepared on the surface of the screw product; The sputtering power is 150-300W, the distance between the target and the substrate is 40-90mm, and the argon gas pressure is 0.5-1.20Pa; The target material is the aluminum / silicon carbide composite material; the substrate is the surface-treated screw; The mass ratio of the aluminum base to the silicon carbide powder is 1:1-5; the molar ratio of carbon to silicon in the silicon carbide powder is 0.8-1.6:

1.

2. The corrosion-resistant coating process for screw products according to claim 1 is characterized by: The aluminum base is selected from one of aluminum-magnesium alloy, aluminum-silicon alloy, aluminum-copper alloy, aluminum-zinc alloy, and aluminum metal ball.

3. The corrosion-resistant coating process for screw products according to claim 1 is characterized in that: The preparation of the surface treated screw comprises the following steps: The screw substrate is added to anhydrous ethanol and subjected to ultrasonic treatment for 30 minutes to remove pollutants on the surface of the substrate to obtain an ultrasonic substrate; the ultrasonic substrate is added to a 0.1 mol / L hydrochloric acid solution and soaked for 10 minutes, and then washed with deionized water and dried to obtain the pretreated screw; The silane coupling agent is added to the ethanol solution and stirred evenly to obtain a silane solution; the pretreated screws are added to the silane solution, and the 10% hydrochloric acid solution is added, stirred for 1 hour until the solvent evaporates, washed with deionized water, and vacuum dried at 80° C. for 1 hour to obtain the surface-treated screws.

4. The corrosion-resistant coating process for screw products according to claim 1 is characterized by: The silane coupling agent is selected from one of vinyl trimethoxysilane, methyl trimethoxysilane, methyl triethoxysilane, (3-aminopropyl) trimethoxysilane and trimethoxychlorosilane.

5. The corrosion-resistant coating process for screw products according to claim 1 is characterized by: The aluminum / silicon carbide composite material is prepared by powder mixing, cold pressing, nitrogen sintering and hot extrusion.

6. The corrosion-resistant coating process for screw products according to claim 5, characterized in that: The cold pressing pressure in the cold pressing treatment is 100-300 MPa; the nitrogen sintering temperature is 500-650° C., and the sintering time is 30-120 min; and the hot extrusion treatment temperature is 400-500° C.

7. The corrosion-resistant coating process for screw products according to claim 1 is characterized by: The preparation of the screw product with the corrosion-resistant coating comprises the following steps: Open the vent valve of the vacuum sputtering chamber, balance the air pressure in the furnace with the atmospheric pressure, and then open the furnace door; clean the equipment cavity, the surface of the magnetron target, the sample and the fixture with alcohol; put the surface-treated screws into a beaker, and ultrasonically clean them with deionized water, acetone and anhydrous ethanol for 10-15 minutes respectively to obtain a clean substrate; rinse the surface of the clean substrate with flowing anhydrous ethanol for 30-50 seconds, blow dry the cleaned substrate with an ear bulb, immediately place it on the sample holder, load it into the sputtering chamber, close the furnace door, evacuate, and start sputtering deposition; Close the furnace door and valve, and start the circulating water system; turn on the gas flow meter power switch, open the gas cylinder, and then turn the flow meter valve to "valve control", adjust the flow rate to 30sccm, and keep it for 10-15min; slowly pump gas until the pressure in the furnace reaches the experimental working pressure; Turn on the sputtering power supply, slowly adjust the gas filling valve until the target surface glows, start pre-sputtering the target, and continue for 10-20 minutes; then adjust the sputtering power and gas pressure, remove the baffle on the surface of the clean substrate, perform sputtering coating, and determine the thickness by recording the sputtering time, and the sputtering time is 6 hours; After the experiment, all valves were closed, and the water cooling system was closed after 1 hour. After the reaction device was cooled, the furnace gas valve was opened to balance the atmospheric pressure inside and outside the furnace, and then the furnace door was opened to obtain the screw products with the corrosion-resistant coating.

8. The corrosion-resistant coating process for screw products according to claim 1, characterized in that: The sputtering power is 100-250W; the distance between the target and the substrate is 50-80mm; and the argon gas pressure is 0.6-1.0Pa.

9. The corrosion-resistant coating process for screw products according to claim 1, characterized in that: The concentration of silane coupling agent is 0.8-1.5 mg / L.

10. A corrosion-resistant coating for a screw product, characterized in that: The corrosion-resistant coating of the screw product is obtained by the process described in any one of claims 1 to 9; the corrosion-resistant coating of the screw product includes the aluminum / silicon carbide composite material and the surface-treated screws; the tensile strength of the aluminum / silicon carbide composite material is 262MPa; the coating deposition rate of the corrosion-resistant coated screw product is 1.42μm / h; the substrate of the corrosion-resistant coated screw product is not corroded under the conditions of 240h of simulated salt spray environment; in the bonding strength test of the corrosion-resistant coated screw product, the bonding strength grade is 5B; the average friction coefficient of the corrosion-resistant coated screw product is 0.125.

Citation Information

Patent Citations

  • Coating for screws of wheel hubs for trucks

    CN107903724A

  • Aluminium-based composite material with high silicon carbide content and preparation method of composite material

    CN104498778A

  • Metal ceramic composite coating for aircraft wing and preparation method thereof

    CN111519180A